Pendidikan Karakter Mahasiswa melalui Sastra Lisan Jepang secara Online - Noviyanti Aneros (Universitas Negeri Semarang, 2022)
This study aims to find values in Japanese mukashibanashi in online media through the Youtube channel, purposing it can be implemented simultaneously in the learning process. Mukashibanashi is a Japanese folk tale. This research is a qualitative descriptive study. The source of the data comes from the web https://www.youtube.com/channel/UCaCiBKglFZkSYXmlWZBDLgw of Japanese folklore. The data collection technique used non-interactive techniques by watching and listening to the mukashibanashi video, summarizing the story, and then taking active notes using the content analysis method. Data validity to test the validity of this study using data triangulation techniques and method triangulation. The data analysis technique uses an interactive analysis model. Data analysis was performed using Miles and Huberman models and Lickona's theory (essential and main characters that must be transferred to the students). There are seven characteristics education found, namely: heart praise, compassion, compassion, cooperation, courage, hard work, and honesty. These values can be used in educating and building student character. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalPendidikan Karakter MahasiswaJapanese Character EducationJapanese Culture ValueJapanese Folk Tale